CASE STUDY: INTERVENSI FISIOTERAPI PADA KONDISI TRIGGER FINGER DENGAN INTERVENSI ULTRASOUND (US) DAN NEUROMUSCULER TAPING UNTUK MENGURANGI NYERI - Permata, Ayu; Rizal, Yose; Triyulianti, Sari; Dwiningtyas, Hannisyah (Jurnal Ilmiah Fisioterapi, 2024)
Background: Trigger finger is a condition when the finger feels stiff when bent or stretched. This condition occurs because the protective layer surrounding the tendons becomes inflamed in the tendons or tissue connecting bones and muscles, causing a painful sensation when the sufferer bends or straightens the fingers. Trigger finger can also cause the finger to feel painful and stiff so that it cannot be moved. Objective: This research is aimed at sufferers of Trigger Finger conditions to reduce pain. Research Method: Case study with a sample size of 1 person suffering from Trigger Finger. Ultrasound intervention and application of Neuromuscular Taping 3 times a week for 2 weeks. This research was conducted at RSI Ibnu Sina Pekanbaru in January – March 2024. The pain measurement tool used the Visual Analogue Scale (VAS). The research design was pre and post test, namely comparing VAS scores before and after the intervention. Results: after 6 treatments for 2 weeks with 3 treatments a week. In the reduce pain results before = 2.5 (mild pain) and after = 1.75 (mild pain); tenderness before = 7.5 (severe pain) and after 4.5 (moderate pain); movement pain before = 6 (severe pain) and after = 3.5 (mild pain). Conclusion: Ultrasound intervention and Neuromuscular Taping are conservative interventions in Trigger Finger treatment that can reduce pain.